2008
DOI: 10.1111/j.1526-4610.2007.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache and Internal Carotid Artery Dissection: Two Cases and Review of the Literature

Abstract: We describe 2 patients with cluster headache attacks associated with a dissection of the ipsilateral internal carotid artery at the extra-intracranial passage. These cases highlight the need for extensive neuroradiological investigation in cluster headache patients when atypical features are present. We also performed a PubMed search to review the current literature data about this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…107,113,116: cases 1 and 2; 118-120, 123).Among considered CLH patients (n = 148), 74.1% of the sample were male and 25.9% female, the M : F ratio being 2.7:1 (100/38, since data on patient gender were missing in 13 cases). The age of symptom onset was 42.8 Ϯ 15.2 years, while the age of correct diagnosis was 47.0 Ϯ 13.4 years.…”
mentioning
confidence: 99%
“…107,113,116: cases 1 and 2; 118-120, 123).Among considered CLH patients (n = 148), 74.1% of the sample were male and 25.9% female, the M : F ratio being 2.7:1 (100/38, since data on patient gender were missing in 13 cases). The age of symptom onset was 42.8 Ϯ 15.2 years, while the age of correct diagnosis was 47.0 Ϯ 13.4 years.…”
mentioning
confidence: 99%
“…In a recent review on secondary cluster headache, 11 out of 63 patients had a carotid/vertebral dissection [3]. A review in 2007 identified 6 patients with ICA dissection presenting with cluster-like features [10] and several more cases have been described [11,12,13,14,15]. In all these patients, headache attacks disappeared within 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…41 The signs and symptoms experienced by the patient in this case report are similar to those described in other examples in medical literature. 15,[42][43][44][45] Internal carotid artery dissection accounts for up to one fifth of ischemic strokes occurring in people under the age of 45 years. It typically occurs in adults at a mean age of 40 years and with a male:female ratio of 1.5.…”
Section: Internal Carotid Artery Dissection Discussionmentioning
confidence: 99%